Detection of endoleaks following thoracic and abdominal aortic endovascular aortic repair: a comparison of standard and dynamic 4D-computed tomography angiography : clinical investigation - Waldeck, Stephan; Overhoff, Daniel; Brockmann, Marc A.; Becker, Benjamin V. (Journal of endovascular therapy, 2023)
Purpose: Endoleaks are a common complication after endovascular aortic repair (EVAR) and thoracic endovascular aortic repair (TEVAR). The detection and correct classification of endoleaks is essential for the further treatment of affected patients. However, standard computed tomography angiography (CTA) provides no hemodynamic information on endoleaks, which can result in misclassification in complex cases. The aim of this study was to compare standard CTA (sCTA) with dynamic, dual-energy CTA (dCTA) for detection and classification of endoleaks following EVAR or TEVAR. - Materials and Methods: This retrospective evaluation compared 69 sCTA diagnostic examinations performed on 50 different patients with 89 dCTA diagnostic examinations performed on 69 different patients. - Results: In total, 15.9% of sCTA examinations and 49.4% of dCTA examinations led to the detection of endoleaks. With sCTA, 20.0% of patients were diagnosed with endoleaks, while with dCTA, 37.7% of patients were diagnosed with endoleaks. With sCTA, mainly Type 1 endoleaks were detected, whereas, with dCTA, the types of detected endoleaks were more evenly distributed. In comparison with the literature, the frequencies of endoleak types detected with dCTA better reflect the natural distribution than the frequencies detected with standard CTA. - Conclusion: Based on the retrospective comparative evaluation, dCTA could pose a valuable supplementary diagnostic tool resulting in a more accurate and realistic detection and classification of suspected endoleaks.
Erstmals online veröffentlicht: 18. Mai 2022
Em Ende des Titels ist ein Bindestrich dargestellt
Gesehen am 30.07.2024